A elaboração do discurso argumentativo por alunos do ensino fundamental - Claudia Barbosa Siqueira (2012)
This dissertation is a study of how argumentation presents itself in the writings of primary school students from a private school in Belo Horizonte, MG, Brazil. The corpus consists of texts written by students between eight and fifteen years of age. The main goal of this study is to enquire whether children and adolescents are able to refine their argumentative capacity and the use of argumentative strategies by means of methodological dynamics which take oral language as a starting point to written production. We work along the hypothesis that students of that age group are able to argue, counter-argue, develop and refine their argumentative competence when properly invited to do so. The works of Oswald Ducrot, Chaim Perelman, Stephen Toulmin and Ingedore Villaça Koch were taken as a basis for reflection upon the chosen theme the work of argumentation in written texts. We tried to understand and to apprehend the linguistic phenomena that integrate argumentative texts. Corpus analysis was founded on theoretical concepts of Textual Linguistics for discourse interpretation and understanding, such as: argumentative structure, argumentative operators, textuality and coherence. This study is also based on Rhetorical Structure Theory (RST), a descriptive theory within Functionalism that investigates relations among text parts: rhetorical relations, or relational propositions or coherence relations. By establishing an interface between Functionalism and Textual Linguistics, the analysis points towards the following results: student writings present defining marks, leading to an argumentative orientation, such as argumentative operators; linguistic processes such as parallelism, polyphony, and referentiation; efficient use of argumentative strategies; counter-argumentation skills.